Leadership in public libraries / Aida Kamaludeen, Amir Muhamad Shafie and Mohamad Hafiz Abdullah - Kamaludeen, Aida; Muhamad Shafie, Amir; Abdullah, Mohamad Hafiz (2014)
Elisabeth Aldstedt and what she learns through her experienced of years in being a leader for a public library. Also, this article explains what it means by leaders in library as visionary, successful manager and also as role model for the people in the library organization.